The association between shift work and depression in hotel workers. Issue 1 (December 2015) - Moon, Hyun; Lee, Sang; Lee, Hee; Lee, Kyung-Jae; Kim, Joo
Abstract Background Shift work is vital in hotel businesses as these businesses run 24 h daily regardless of holidays to accommodate customers. The number of shift workers in hotel businesses is expected to increase consistently and it is crucial to study the impact of shift work on hotel workers' mental health. This study, therefore, aims to examine the association between depression and shift work in hotel workers. It especially focuses on investigating whether there is a difference in how closely these two are related depending on shift types. Methods A survey was conducted with 768 hotel workers who worked at two first-class hotels in Seoul. Out of 659 respondents total (response rate of 85.8 %), 506 respondents were selected as the final research subjects, excluding 153 respondents whose responses were incomplete. The survey was composed of questionnaires related to general characteristics, work-related characteristics, shift work, shift type, and depression level. The Korean Center for Epidemiologic Studies Depression (CES-D) Scale was used to evaluate the subjects' depression level. Multiple logistic regression analysis was conducted with depression as a dependent variable and shift type as an independent variable after relevant general and work-related characteristics were adjusted to examine the relationship between shift type and depression. Results After adjustment for relevant general and work-related characteristics, hotel workers had a significantly higher likelihood of belonging to the depression group than those with a fixed day shift, across all three shift types: rotating day shift (OR = 2.22, 95 % CI = 1.05–4.61), rotating night shift (OR = 2.63, 95 % CI = 1.11–6.24), and fixed night shift (OR = 3.46, 95 % CI = 1.02–11.74). Conclusions The results showed that shift work was significantly related to depression in hotel workers and the risk of depression clearly differed among shift types. In particular, fixed night shift workers were most vulnerable to depression. Rotating day shift workers without night work could also have a higher risk of depression.